Minimally invasive ethyl cellulose ethanol ablation in domesticated cats with naturally occurring head and neck cancers: Six cats - Lai, Yen‐Hao Erik; Morhard, Robert; Ramanujam, Nirmala; Nolan, Michael W. (Veterinary & comparative oncology, 2021)
It is difficult to retain tumoricidal doses of ethanol in large or unencapsulated tumours without causing intoxication or damaging surrounding tissue. Ethyl cellulose‐ethanol ablation (ECEA) overcomes this limitation by trapping ethanol intratumorally. To evaluate the safety of ECEA and to develop a clinically feasible workflow, a single‐arm pilot study was performed in cats with lingual/sublingual squamous cell carcinoma (SCC). Six cats underwent intratumoral injection of 6% ethyl cellulose in ethanol. Subjects were observed overnight. There was mild bleeding and transient hyperthermia, and injection site pain and swelling that improved with anti‐inflammatory drugs. Serum ethanol was minimally elevated; the mean concentration peaked 1 hour after injection (129 +/− 15.1 nM). Cats were rechecked at weeks 1 and 2; booster treatments were given in cats (n = 3) with stable quality of life and partial response to therapy. Recheck examinations were then performed monthly. The longest tumour dimension increased in each animal (progressive disease via cRECIST); however, estimated tumour volume was reduced in 3 of 6 cats, within 1 week of ECEA. All cats were euthanized (median survival time 70 days) because of local tumour progression and/or lingual dysfunction that was likely hastened by ECEA. ECEA is not a viable treatment for feline lingual/sublingual SCC; tumour volume was effectively reduced in some cats, but the simultaneous loss of lingual function was poorly tolerated. Further optimization may make ECEA a useful option for SCC at other oral sites in the cat, and for head and neck malignancies in other species.